Análisis Crítico del discurso de la caricatura periodística de Diario El Comercio en estado de emergencia por COVID-19, periodo marzo-agosto 2020. - Hernández Pozo, Mario Fernando (2023)
The present research called "Critical analysis of the discourse of the journalistic cartoon of the newspaper El Comercio in state of emergency by Covid-19, period March-August 2020" establishes its bases in the critical analysis of the discourse raised by Teun Van Dijk and making use of the content analysis to achieve to know and establish each of the parameters to be analyzed. It is for this reason that through the documentary review technique, a total of 182 cartoons were identified in the mentioned period where through its cartoonists, the newspaper El Comercio broadcast in its visual arts everything that happened in a satirical, burlesque and intriguing way before a completely new event such as the covid-19. After dividing each of the cartoons by thematic axes, a macro and micro discursive analysis was carried out in which the sample of 24 cartoons was analyzed with each of the parameters, and seeking a contrast of the results obtained with the criteria of experts on the subject in this case Xavier Bonilla (Bonil) expert cartoonist and Rubén Darío Buitrón expert on the subject of critical analysis of the discourse where it was agreed that the cartoon was a fast and new medium in which the readers found out the news of the newspapers. readers learned about the country's current events in such a critical moment where the government of Lenin Moreno did not act effectively, being corruption one of the most relevant thematic axes in 6 months of broadcasting of these visual arts that sought to inform in a fast and different way.